α-Azido Ketones, Part 8: Base-Induced Coupling of α-Azido Ketones with a 1,2-Diaza-1,3-diene as a Michael Acceptor - Juhász-Tóth, Éva; Favi, Gianfranco; Attanasi, Orazio A.; Bényei, Attila C.; Patonay, Tamás (Synlett, 2014)
Carbanions generated from various acyclic and cyclic α-azido ketones in the presence of bases were reacted with ethyl 3-[(carbamoylimino)amino]but-2-enoate as a Michael acceptor to give the corresponding adducts. The adducts of acyclic azides were unstable and eliminated hydrazoic acid to give the corresponding ethyl 2-[1-[(carbamoylamino)imino]ethyl]-4-oxo-4-phenylbut-2-enoates as (E,E/Z,E)-diastereomeric mixtures. The relative configuration of these diastereomers was determined by X-ray analysis. Adducts of cyclic α-azido ketones were obtained in diastereomerically pure form, with the exception of 2-azidobenzosuberone.
Keywords: ketones; azides; Michael additions; carbanions; diazadienes